Corporate Social Responsibility and Urban Development Lessons from the South - Murphy, David; Keivani, Ramin; Werna, Edmundo (U.K. Palgrave Macmillan, 2009)
Chapter 1. Corporate Social Responsibilty - David Murphy and Austine Ng'ombe